Digital storytelling authoring tool to support transformative learning in education - Quah, Chia Yi (2025)
Digital storytelling has been a powerful and innovative pedagogical tool that cultivates 21st century skills through an integrated and constructivist approach. Digital storytelling engages learners in reflection which is the prerequisite to meaningful learning and transformative learning. Transformative learning enhances critical-thinking skills to help learners relate new knowledge to their own life experiences through reflective practices. While there are numerous existing pedagogical digital storytelling authoring tools developed with emerging technologies such as AR (Augmented Reality and VR (Virtual Reality), a paucity of these tools is designed to facilitate transformative learning. In this research, we explore different emerging technologies to be incorporated, and how to design a digital storytelling authoring tool that supports transformative learning. Systematic literature review on digital storytelling authoring tools in education from last 10 years was conducted to identify research direction. Findings suggested that while research has explored Artificial Intelligence (AI) in language learning and reflective practices, its integration to enhance both simultaneously remains underexplored. An artificial intelligence storytelling chatbot, Dutch Lady, was designed and evaluated during the Malakka Dutch hybrid exhibition to explore how to design to support reflection and to investigate user acceptance towards chatbot as a storytelling authoring tool. Interviews and user observations were conducted with 13 participants from physical exhibition and 13 participants from digital exhibition. Findings suggested that Dutch Lady, the AI storytelling chatbot enhanced cultural heritage learning experience. Technical infrastructure and environment (digital or physical spaces) are significant in shaping user engagement. To effectively support reflection, a storytelling chatbot needs to be able to ask in-depth questions and respond in a context-aware and emotionally intelligent manner. Tale-It, an AI-assisted storytelling authoring tool for reflection was developed and evaluated with four international schools in Selangor. The user study was conducted with 278 students ranging from 11 to 16 years old. Comparative study was conducted to identify learning outcome and measure level of reflection in participants engaging with non-AI Tale-It and AI-assisted Tale-It. Findings revealed that AI-assisted Tale-It is effective in enhancing organisation, content and vocabulary of a story. Additionally, the reflection questions in AI-assisted Tale-It prompted in three cycles successfully triggered reflective practices, prompting participants to not only reflect on their work but also to set future goals for improvement. The contribution of this research is a Transformative Reflection Framework that facilitates structured reflection during learning process, leading to transformation learning. In addition, the research provides design guidelines for educational digital storytelling authoring tools.